2009
DOI: 10.1007/s10661-009-1089-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring bathing beach water quality using composite sampling

Abstract: Michigan water quality standards for public bathing beaches require local health departments to collect and analyze a minimum of three water samples for Escherichia coli during each sampling event. The geometric mean number of E. coli colonies is then compared to the 300 colonies per 100 ml standard to determine compliance. This article compares the results of the currently mandated procedure to a composite sampling method, whereby the three samples are mixed in equal volumes and analyzed once. This effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Composite sampling can significantly reduce the analytical costs by reducing the number of samples while increasing the likelihood of capturing the high variation inherent to microbe concentrations in water that would likely be missed with a single sample. Previous surface water studies have shown that composite samples provide better protection of human exposure to elevated bacteria concentrations compared to a single sample (Reicherts and Emerson, 2010;. However, even using composite samples, a sampling strategy requiring five sampling events per year will not adequately protect produce safety considering the high variability potential of bacteria in water (Boehm, 2007;Verhougstraete and Rose, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite sampling can significantly reduce the analytical costs by reducing the number of samples while increasing the likelihood of capturing the high variation inherent to microbe concentrations in water that would likely be missed with a single sample. Previous surface water studies have shown that composite samples provide better protection of human exposure to elevated bacteria concentrations compared to a single sample (Reicherts and Emerson, 2010;. However, even using composite samples, a sampling strategy requiring five sampling events per year will not adequately protect produce safety considering the high variability potential of bacteria in water (Boehm, 2007;Verhougstraete and Rose, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a single sample may not provide an adequate representation of the true microbial water quality in an irrigation water canal. Water quality scientists have also noted the implications of a single sample versus multiple samples for management actions (e.g., opening or closing of a beach) (Bertke, 2007;Reicherts and Emerson, 2010). Kinzelman et al (2006) determined that compositing multiple lake water samples and assaying with a single test was not statistically different (P > 0.02) than analyzing multiple individual samples and reporting an average; both approaches called for similar management actions.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, analysis samples can be aggregated from numerous smaller volumes or aliquots (“composite” samples) collected over spatial or temporal intervals. The benefits and limitations of composite sampling have been examined in a number of microbiological applications (Jarvis, 2007; Reicherts & Emerson, 2010) that seek reduced cost or increased representativeness of the data.…”
Section: Introductionmentioning
confidence: 99%
“…In enumeration of FIB by culture-based methods in water samples, results from composite samples have been shown to be significantly correlated to the arithmetic means of single-sample results and to yield similar beach closure decisions (1,6,10). Moreover, analysis of a single composite sample has been estimated to be nearly 40% less expensive than multiple single-sample culture analyses (10). Recent studies have indicated that qPCR-based measurements of FIB are statistically associated with gastrointestinal illness among swimmers (15,16,17), and composite sampling could generate significant savings for water quality monitoring programs using qPCR.…”
mentioning
confidence: 99%
“…Compositing involves mixing equal volumes of spatially discrete samples and analyzing the homogenate. In enumeration of FIB by culture-based methods in water samples, results from composite samples have been shown to be significantly correlated to the arithmetic means of single-sample results and to yield similar beach closure decisions (1,6,10). Moreover, analysis of a single composite sample has been estimated to be nearly 40% less expensive than multiple single-sample culture analyses (10).…”
mentioning
confidence: 99%